PENGARUH PEMBERIAN KAPSUL BUBUK DAUN KELOR (MORINGA OLEIFERA LEAVES POWDER) TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA MAHASISWA PROGRAM STUDI KEBIDANAN (S1) FITKES UNJANI - Fitri Nurhayati; Nur Endah, Siti; Drajat, Aulia (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: One of the biggest public health problems in the world, especially among adolescents, is anemia. The prevalence of anemia in adolescents in the world is 4.8 million, in Indonesia there is an increase of 11.8%. Basic Health Research data report (RISKESDAS) in 2013 adolescents experienced anemia of 37.1%, an increase to 48.9% in 2018. Moringa leaf powder capsules (moringa oleifera leaves powder) can be an alternative to increase hemoglobin levels. Objective: The purpose of this study was to determine the effect of giving Moringa oleifera leaves powder capsules on increasing hemoglobin levels in students of the Faculty of Health Science and Technology, Bachelor of Midwifery Study Program Method: The type of research used was quasi-experimental with a one-group pre-test-post-test design. The sample of this study was 30 students at the Faculty of Health Science and Technology, Undergraduate Midwifery Study Program. This study used the intervention of giving moringa leaf powder capsules (moringa oleifera leaves powder) for 2 weeks at a dose of 500 mg/day 2x1 in the morning and evening, the research instrument used a hemoglobinometer digital portable and observation sheets to see the results of examination of hemoglobin levels. Univariate and bivariate analysis with Paired Sample Test using Shapiro-Wilk. Results: The results of the study stated that there was an increase in the mean value before the intervention of (10.97gr/dl) and after the intervention Background: One of the biggest public health problems in the world, especially among adolescents, is anemia. The prevalence of anemia in adolescents in the world is 4.8 million, in Indonesia there is an increase of 11.8%. Basic Health Research data report (RISKESDAS) in 2013 adolescents experienced anemia of 37.1%, an increase to 48.9% in 2018. Moringa leaf powder capsules (moringa oleifera leaves powder) can be an alternative to increase hemoglobin levels. Objective: The purpose of this study was to determine the effect of giving Moringa oleifera leaves powder capsules on increasing hemoglobin levels in students of the Faculty of Health Science and Technology, Bachelor of Midwifery Study Program Method: The type of research used was quasi-experimental with a one-group pre-test-post-test design. The sample of this study was 30 students at the Faculty of Health Science and Technology, Undergraduate Midwifery Study Program. This study used the intervention of giving moringa leaf powder capsules (moringa oleifera leaves powder) for 2 weeks at a dose of 500 mg/day 2x1 in the morning and evening, the research instrument used a hemoglobinometer digital portable and observation sheets to see the results of examination of hemoglobin levels. Univariate and bivariate analysis with Paired Sample Test using Shapiro-Wilk. Results: The results of the study stated that there was an increase in the mean value before the intervention of (10.97gr/dl) and after the intervention